1992
DOI: 10.1007/bf01309702
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the HIV-1 Nef protein in the baculovirus system: investigation of anti-Nef antibodies response in human sera and subcellular localization of Nef

Abstract: The nef gene of HIV-1 was expressed in insect cells using the eucaryotic baculovirus system. The recombinant Nef protein frequently reacted with seropositive sera of HIV-1 and HIV-2 infected patients. Anti-Nef antibodies in HIV-1 seronegative high risk groups individuals were only occasionally seen. Confocal laser scanning microscopy demonstrated that Nef is present both in the cytoplasm and in the nucleus, indicating that Nef might directly function on gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1993
1993
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…The 26-kDa Nef protein is in agreement with the observations of other authors (Kaminchik et al, 1991 ;Wolber et al, 1992). The additional 31-kDa form might be due to posttranslational modifications, as discussed recently (Kienzle et al, 1992b). The 24-kDa Nef may arise as the result of a second internal translationinitiation event (Kaminchik et al, 1991).…”
Section: Oligomerization Of Nef Under Non-reducing or Alkylating Condsupporting
confidence: 81%
See 2 more Smart Citations
“…The 26-kDa Nef protein is in agreement with the observations of other authors (Kaminchik et al, 1991 ;Wolber et al, 1992). The additional 31-kDa form might be due to posttranslational modifications, as discussed recently (Kienzle et al, 1992b). The 24-kDa Nef may arise as the result of a second internal translationinitiation event (Kaminchik et al, 1991).…”
Section: Oligomerization Of Nef Under Non-reducing or Alkylating Condsupporting
confidence: 81%
“…Our own data, generated by confocal laser-scanning microscopy (Kienzle et al, 1992b), suggest that the baculovirus-derived Nef protein is capable of being secreted in vesicles from insect cells. Baculovirus-derived Nef has been shown to be myristoylated (Matsuura et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were maintained in RPMI 1640 (Seromed) as described [5]. As outlined recently, the insect cell line SF 158 was lytically infected with wild-type baculovirus or with the Nef baculovirus vAYFl or vD3F3 [32], both encoding the nefgene of HIV-1 LA1 [33]. SX22-1 cells were derived from the CD4 positive HeLa T4 cell line by stable transfection with a lacZ reporter plasmid (T. Klimkait, unpublished results).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Nef-specific antibodies and cytotoxic T lymphocytes are present in the circulation of two-thirds of HIV-seropositive individuals (16)(17)(18) indicating that Nef may be present extracellularly in vivo. In vitro, studies show that HIV-infected cells release Nef protein in vesicles as observed by confocal laser-scanning microscopy and by its sedimentation behavior on ultracentrifugation (19,20). Further, HIV-1 Nef protein derived from yeast cells has been found in the extracellular medium in concentrations of up to 40 g͞ml during stress (21).…”
mentioning
confidence: 94%